EXPLORING THE CONCEPTUAL MODEL OF PUBLIC PRIVATE PARTNERSHIP FOR LOCAL TOURISM DEVELOPMENT - Damas Dwi Anggoro; Hanifa Maulani Ramadhan; Rispa Ngindana (DIA: Jurnal Administrasi Publik, 2022)
The concept of Public-Private Partnerships (PPPs) has been accepted as one viable alternative to promote infrastructure development. Yet, recently some government institutions have applied PPPs for developing local tourism sites for their region. The situation is going to be more complex when the PPPs deal with some non-physical attributes and generate several shortcomings. Therefore the need for a specific model to cover PPPs as the concept and tourism development as its substance becomes essential. This research attempts to explore the model by using a specific review of the recent kinds of literature and theories. It is conducted by contextual approaches intended to adjust to Indonesian tourism development. The result of this research has described the specific model which is constructed from a series of literature discussions from previous studies. It has been designed to minimize the weakness and vulnerable points of PPPs for tourism development.